The Effect of Entrepreneurial Performance among the Mango Growers in Salem District of Tamil Nadu - N., Manivannan; Natarajan, M. (Indian Journal of Extension Education, 2020)
The study was undertaken with the objectives of analysis of entrepreneurial performance of mango growers in Salem district of Tamil Nadu. Sankari Block was selected based on the maximum area under mango cultivation.A sample size of 120 mango cultivating farmers was selected by using the proportionate random sampling technique. The required data were collected by personal interview utilizing a well-structured and pre-tested interview schedule. The result revealed that the 60 per cent of the respondents came under a medium level of entrepreneurial performance of mango farming. Around one-fourth of the respondents came under low level of entrepreneurial performance and only a small proportion of the respondents (13.33%) were under high level of entrepreneurial performance of mango cultivation.